Anti-cancer Activity Evaluation of Naphthalenonic and Chromanonic Spiroisoxazoline Derivatives as Selective COX-2 Inhibitors on HT29 Cell Lines - Kalhor, Hourieh; Movahhed, Tahereh Komeili; Mousavi, Shokoufeh; Qomi, Masoumeh Sadri; Abolhasani, Ahmad; Mirani, Masoumeh; Rad, Minoo Hosseini; Heidari, Fatemeh; Abolhasani, Hoda (Clinical Cancer Drugs, 2024)
BackgroundCyclooxygenase-2 (COX-2) is induced in response to proinflammatory conditions, and it is not only a key enzyme in the inflammatory process, but also seems to be highly expressed in various types of cancer cells. On the other hand, it is well documented that chemical compounds with spiro scaffolds in their structure could be effective chemical agents against cancer types.ObjectiveIn this study, the cytotoxicity effects of spiroisoxazoline derivatives containing a spiro-bridge of naphthalinone and chromanone were investigated.MethodsThe cytotoxicity effects of compounds 7a-7h were evaluated by performing the MTT assay on the HT-29 (colorectal cancer), MCF-7 (breast cancer), and HEK-293 (normal kidney) cell lines. After that, a compound with high yield and remarkable cytotoxic activity was selected to analyze the cell cycle and apoptosis mechanism.ResultsThe most effective cytotoxic activity was observed on HT-29 and MCF-7 cell lines of compounds 7b (IC50 value: 1.07±0.28 µM) and 7f (IC50 value: 11.92±1.07 µM). None of the compounds had a toxic effect on normal HEK-293 cells, except for compound 7g with an IC50 value of 21.30±16.14 µM, whose effect was much lower than that of cisplatin and doxorubicin, known as anti-cancer agents. Subsequently, compound 7e with significant yield and cytotoxic activity was investigated to evaluate cell cycle and apoptosis. The result showed that compound 7e induced significant G0/G1 cell cycle arrest and apoptosis in HT-29 cells.ConclusionThe selective COX-2 inhibitor compounds with spiroisoxazoline core structure could be suitable scaffolds for cytotoxic effects.
Keywords: HT-29